Effects of impact angles and shapes on CAI strength of composite honeycomb structure - Duan, Yuechen; Sun, Siyuan; Huang, Guibin; Zhan, Zhiren; Yang, Jun; Wang, Tingting (International journal of crashworthiness, 2025)
The Compression After Impact (CAI) strength can enhance safety and reliability in engineering applications, improve simulation and prediction capabilities. It is also an important indicator for assessing the damage tolerance capacity of composite structures. The CAI strength is directly influenced by low-velocity impact, which holds significant scientific research implications for evaluating structural safety, optimising design and enhancing material properties. Analysing different impact shapes and angles provide a closer representation of real-world engineering scenarios, rendering results more reliable and valuable. The subject is a CFRP panel with Nomex honeycomb sandwich structure, where both the skin and core are composed of composite materials. Low-velocity impact and compression after impact tests were conducted to establish an integrated and refined finite element model for the CFRP panel with Nomex honeycomb structure. The model's validity was confirmed by comparing with test results. Various impact shapes and angles were investigated using the established model to examine their influence on the CAI strength of the composite honeycomb sandwich structure. The following conclusions were drawn: (1) Sharper impactors result in lower CAI strength and higher compressive failure displacement. (2) The CAI strength, normalised CAI strength, and failure displacement of the structure increase with the impact angles. Among the tested angles, the 30° impact angle induced the least damage, exhibiting the highest CAI strength, normalised CAI strength, and failure displacement. However, as the angle increases, energy losses between the impactor and specimen increase, impact energy decrease. Consequently, the structural indicators decrease compared to the 30° impact angle.